2013
DOI: 10.1080/09654313.2013.782389
|View full text |Cite
|
Sign up to set email alerts
|

Harmony and Melody in Discourse on European Cohesion

Abstract: International audienceFrom a corpus constituted by the five Cohesion Reports written by the European Commission, the article, using the methods of textual analysis, highlights the production of a European discourse on the territories participating to a process of institutionalization. Thus, starting from various authors analyses who validate the idea of institutionalization, the authors propose here to further explore this idea, using a method based on a lexical analysis software. The aim is then, on the one h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…As previous research has shown, this approach is valuable in providing knowledge of how the concept of solidarity is mobilised in different ways in different textual sources (for a similar approach with different empirical material see Prokkola, 2020;Zappettini, 2019; for an analysis of similar EU textual material on different concepts, see Damurski and Oleksy, 2018). Elissalde et al (2014) as well as Zappettini (2019) have also shown how key analytical categories (discourse topics) as well as argumentations can be mapped with this methodology. Varr o ( 2008) has also pointed out how through an analysis of such discourses we can also understand politics of re-scaling.…”
Section: Analytical Framework and Methodologymentioning
confidence: 99%
“…As previous research has shown, this approach is valuable in providing knowledge of how the concept of solidarity is mobilised in different ways in different textual sources (for a similar approach with different empirical material see Prokkola, 2020;Zappettini, 2019; for an analysis of similar EU textual material on different concepts, see Damurski and Oleksy, 2018). Elissalde et al (2014) as well as Zappettini (2019) have also shown how key analytical categories (discourse topics) as well as argumentations can be mapped with this methodology. Varr o ( 2008) has also pointed out how through an analysis of such discourses we can also understand politics of re-scaling.…”
Section: Analytical Framework and Methodologymentioning
confidence: 99%
“…In addition, it being a polysemic term, the notion of territory, in its different lexical forms and, in particular, as a qualifier (territorial), has become a major reference both in the EU vocabulary and in applied research on spatial development at the EU scale. In the periodic EU 'Cohesion reports' for instance, we can identify five usages and meanings: a country, a unit to manage public funding, a space with peculiar features, a political project ('territorial cohesion'), and a term related to impact assessments of actions on space4 (Elissalde et al, 2013).…”
Section: From Space To Territory: Looking For a Fitmentioning
confidence: 99%
“…3 This survey was conducted in 2011 within the project ESPON 2013 entitled Capitalisation and dissemination of ESPON concepts (CaDEC).…”
Section: Espon (European Observation Network For Territorial Developmmentioning
confidence: 99%
“…First of all, the institutional setting encourages the European authorities to bolster their legitimacy by developing a specific discourse, which is relatively stable over time and is upheld by recurrent notions. However contingent changes in political orientations negotiated with the Member States in the course of time lead to alterations in the meaning of these notions [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation